Growth hormone signaling and action in obese versus lean human subjects - Høgild, Morten Lyng; Bak, Ann Mosegaard; Pedersen, Steen Bønløkke; Rungby, Jørgen; Frystyk, Jan; Møller, Niels; Jessen, Niels; Jørgensen, Jens O. L. (American journal of physiology: endocrinology and metabolism, 2019)
Growth hormone (GH) levels are blunted in obesity, but it is not known whether this relates to altered GH sensitivity and whether this influences the metabolic adaptation to fasting. Therefore, we investigated the effect of obesity on GH signal transduction and fasting-induced changes in GH action. Nine obese (BMI 35.7 kg/m 2 ) and nine lean (BMI 21.5 kg/m 2 ) men were studied in a randomized crossover design with 1) an intravenous GH bolus, 2) an intravenous saline bolus, and 3) 72 h of fasting. Insulin sensitivity (hyperinsulinemic, euglycemic clamp) and substrate metabolism (glucose tracer and indirect calorimetry) were measured in studies 1 and 2. In vivo GH signaling was assessed in muscle and fat biopsies. GH pharmacokinetics did not differ between obese and lean subjects, but endogenous GH levels were reduced in obesity. GH signaling (STAT5b phosphorylation and CISH mRNA transcription), and GH action (induction of lipolysis and peripheral insulin resistance) were similar in the two groups, but a GH-induced insulin antagonistic effect on endogenous glucose production only occurred in the obese. Fasting-induced IGF-I reduction was completely abrogated in obese subjects despite a comparable relative increase in GH levels (ΔIGF-I: lean, −66 ± 10 vs. obese, 27 ± 16 µg/l; P < 0.01; ΔGH: lean, 647 ± 280 vs. obese, 544 ± 220%; P = 0.76]. We conclude that 1) GH signaling is normal in obesity, 2) in the obese state, the preservation of IGF-I with fasting and the augmented GH-induced central insulin resistance indicate increased hepatic GH sensitivity, 3) blunted GH levels in obesity may protect against insulin resistance without compromising IGF-I status.